Polycystin-1 regulates tendon-derived mesenchymal stem cells fate and matrix organization in heterotopic ossification - Yi Li Xu; Mei Huang; Yang Zhang; Xin Ying Su; Min Huang; Nan Yu Zou; Yu Rui Jiao; Yu Chen Sun; Ling Liu; Yong Hua Lei; Chang Jun Li (Bone Research)
Abstract Mechanical stress modulates bone formation and organization of the extracellular matrix (ECM), the interaction of which affects heterotopic ossification (HO). However, the mechanically sensitive cell populations in HO and the underlying mechanism remain elusive. Here, we show that the mechanical protein Polysyctin-1 (PC1, Pkd1) regulates CTSK lineage tendon-derived mesenchymal stem cell (TDMSC) fate and ECM organization, thus affecting HO progression. First, we revealed that CTSK lineage TDMSCs are the major source of osteoblasts and fibroblasts in HO and are responsive to mechanical cues via single-cell RNA sequencing analysis and experiments with a lineage tracing mouse model. Moreover, we showed that PC1 mediates the mechanosignal transduction of CTSK lineage TDMSCs to regulate osteogenic and fibrogenic differentiation and alters the ECM architecture by facilitating TAZ nuclear translocation. Conditional gene depletion of Pkd1 or Taz in CTSK lineage cells and pharmaceutical intervention in the PC1-TAZ axis disrupt osteogenesis, fibrogenesis and ECM organization, and consequently attenuate HO progression. These findings suggest that mechanically sensitive CTSK-lineage TDMSCs contribute to heterotopic ossification through PC1-TAZ signaling axis mediated cell fate determination and ECM organization.